Improving positive work behavior of back office employees at sharia microfinance institutions with involvement in religious work life to anticipate fraud - Arif Budiharjo; Komala Andriyani; Dzakiya Salma Kamila; Norraidah Abu Hasan (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - This research aims to determine how efforts to anticipate employee fraud, especially in the back office, are made through human resource development management. How HRD develops the conceptualization of quality work life with religiosity-based organizational cohesiveness nuances in strengthening the positive work behavior patterns of the back office so that fraud does not occur.Method - This research is a qualitative case study with the object of research at SMFIs. Data were obtained using in-depth interviews, observations, and by taking notes. The analysis techniques used were triangulation, visualization of results and patterns of matching between findings with previous research results and existing theories.Result - The research results are the conceptual development of quality work life nuanced cohesion with religiosity.Implication - The recommendations of this study are to strengthen the positive work behavior of Back Office Employees to anticipate fraud. And other recommendations to strengthen Religiosity Organizational Cohesion on the Quality of Work Life with Employee Involvement.Originality - This research is a study that solves the problem of negative behavior with an HR development approach, namely trying to color the Quality of Work Life with Religiosity Organizational Cohesion.